Entrepreneurial Mindset and Self-Efficacy as Mechanisms Linking Entrepreneurship Education to Intention - Soelaiman, Lydiawati; Halim, Christianson; Pamungkas, Ary Satria (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2026)
The persistently elevated unemployment rate among Indonesian university graduates highlights the urgent need for sustainable alternative solutions. At universities, optimizing entrepreneurship education is one strategic approach that can be implemented. Although entrepreneurship education is widely assumed to stimulate students’ entrepreneurial intention, prior empirical evidence remains inconclusive, with studies reporting inconsistent outcomes. This study explores how entrepreneurship education contributes to students’ entrepreneurial intention by considering the roles of entrepreneurial mindset and self-efficacy within the Theory of Planned Behavior framework. The study collected primary data from 130 university students in West Jakarta who had completed an entrepreneurship course. Respondents were selected using purposive sampling, and the data were collected through an online questionnaire. The proposed research model was analyzed using PLS-SEM. The results suggest that exposure to entrepreneurship education is associated with stronger entrepreneurial intention among students, both directly and indirectly, with entrepreneurial mindset and self-efficacy serving as mediators. These findings lend empirical support to TPB and emphasize the importance of integrating cognitive and affective dimensions within entrepreneurship education to pursue entrepreneurial careers.